META-ANALISIS PENERAPAN METODE BERMAIN PERAN TERHADAP KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR - Siti Hanifa Ari Utami; Haryadi Haryadi (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study is to re-analyze the application of the role playing method to the speaking skills of elementary school students.The research method used is meta-analysis by summarizing various research results by examining the parts of each study and the relationship between each study to obtain in-depth conclusions on the research studied with a sample of 10 national journals that are relevant to the title of the research conducted. The data collection technique was carried out by searching electronic journals through Google Scholar with the keywords "role playing method", "speaking skills", "elementary school students", "speaking skills". Data were analyzed using qualitative descriptive analysis.The results of the study found that the role playing learning method had an effect on the speaking skills of elementary school students ranging from the lowest 7.86% to the highest 94.25% with an average of 32%. From the data analysis above, the application of the role playing method has a major influence on the speaking skills of elementary school students.